(untitled) (American Journal of Economics and Business Innovation, 2024)
The paper examines the determinants of bank stability in Nigeria over the 2000 to 2021 period. The analysis was conducted using the ZSCORE as the measure of bank stability in Nigeria alongside the regulatory capital ratio, cost-to-income, non-performing loans, loan-to-deposit, bank concentration, and the share of domestic private credit to GDP as the determinants of bank stability. The model was estimated using the time-series ordinary least square regression method. The results show that the regulatory capital ratio, cost-to-income, non-performing loans, loan-to-deposit, bank concentration, and the share of domestic private credit to GDP are all significant determinants of bank stability in Nigeria. More specifically, regulatory capital ratio, cost-to-income ratio, non-performing loans, and domestic private credit are negative measure of bank stability, while loan-to-deposit ratio and bank concentration are positive determinants of bank stability in Nigeria.